2017
DOI: 10.18632/oncotarget.14520
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular brachytherapy combined with portal vein stenting and transarterial chemoembolization improves overall survival of hepatocellular carcinoma patients with main portal vein tumor thrombus

Abstract: Hepatocellular carcinoma (HCC) patients with main portal vein tumor thrombus have a median survival time of only about 4 months. We therefore compared the safety and efficacy of endovascular brachytherapy (EVBT) and sequential three-dimensional conformal radiotherapy (3-DCRT). From a cohort of 176 patients, we treated 123 with EVBT using iodine-125 seed strands (group A) and the remaining 53 with sequential 3-DCRT (group B). Overall survival, progression free survival and stent patency characteristics were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
14
1
Order By: Relevance
“…Wang [31] reported that the e cacy of radiotherapy combined with TACE was better than that of TACE or TACE combined with sorafenib for HCC patients with type III PVTT. However, it was found that the MST of EVBT combined with TACE (11.7 months) was longer than that of radiotherapy combined with TACE (9.5 months) for the treatment of HCC with type III PVTT [20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wang [31] reported that the e cacy of radiotherapy combined with TACE was better than that of TACE or TACE combined with sorafenib for HCC patients with type III PVTT. However, it was found that the MST of EVBT combined with TACE (11.7 months) was longer than that of radiotherapy combined with TACE (9.5 months) for the treatment of HCC with type III PVTT [20].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown improved e cacy of EVBT combined with TACE versus TACE alone, TACE combined with portal vein stent implantation, and TACE combined with external radiotherapy [17][18][19][20] for the treatment of HCC complicated with type III PVTT. However, type IV PVTT and type III PVTT with invasion of all second intrahepatic portal vein branches were all excluded from these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, this approach is particularly useful for treating patients with unresectable cancer. [ 1 , 2 ] In this study, we explored the treatment benefit of a novel 125I seeds gastric tube in three patients with early inoperable EC. Briefly, the 125I seeds were placed in the gastric tube using a three-dimensional treatment planning system (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…If effective treatment is not available, the median survival time of these patients is only 2.7-4.0 months [3]. In recent years, portal vein stenting (PVS) combined with 125 I implantation has achieved significant effects in treating main portal vein tumour thrombus [4][5][6][7]. Stent implantation in the main portal vein can effectively alleviate portal vein pressure, relieve clinical symptoms, and improve quality of life [8].…”
Section: Introductionmentioning
confidence: 99%